Presence of West Nile Virus in Horses (Equus caballus) in two wetlands in the province of the Ríos, 2007 to 2009 - Coello Peralta, Roberto; Mosquera Martínez., Carlos; González González., Manuel (Revista Universidad de Guayaquil, 2011)
In orden to know the presence of West Nile Virus (WNV) in horses of Ecuador. Was investigated in: The Abras de Mantequilla and Jauneche. For the theme of this research is first conducted a census of the equine population in the areas studied, which was 273 animals. Then the samples were taken, later to be processed on the thread of Virology, National Institute of Hygiene and Tropical Medicine “Leopoldo Izquieta Perez” for the determination of antibodies to WNV by ELISA. The reactive samples were sent to the CDC in Puerto Rico to be confirmed by neutralization test by reducing the number of plates (NTRP). Of the 189 samples tested, 15 were reactive by ELISA of which 5 were confirmed by (NTRP).